Aplysia allatotropin-related peptide and its newly identified d-amino acid–containing epimer both activate a receptor and a neuronal target - Checco, James W. (J Biol Chem, 2018)
l- to d-residue isomerization is a post-translational modification (PTM) present in neuropeptides, peptide hormones, and peptide toxins from several animals. In most cases, the d-residue is critical for the biological function of the resulting d-amino acid–containing peptide (DAACP). Here, we provide an example in native neuropeptides in which the DAACP and its all-l-amino acid epimer are both active at their newly identified receptor in vitro and at a neuronal target associated with feeding behavior. On the basis of sequence similarity to a known DAACP from cone snail venom, we hypothesized that allatotropin-related peptide (ATRP), a neuropeptide from the neuroscience model organism Aplysia californica, may form multiple diastereomers in the Aplysia central nervous system. We determined that ATRP exists as a d-amino acid–containing peptide (d2-ATRP) and identified a specific G protein–coupled receptor as an ATRP receptor. Interestingly, unlike many previously reported DAACPs and their all-l-residue analogs, both l-ATRP and d2-ATRP were potent agonists of this receptor and active in electrophysiological experiments. Finally, d2-ATRP was much more stable than its all-l-residue counterpart in Aplysia plasma, suggesting that in the case of ATRP, the primary role of the l- to d-residue isomerization may be to protect this peptide from aminopeptidase activity in the extracellular space. Our results indicate that l- to d-residue isomerization can occur even in an all-l-residue peptide with a known biological activity and that in some cases, this PTM may help modulate peptide signal lifetime in the extracellular space rather than activity at the cognate receptor.